Remodeling effects of carotid artery stenting versus endarterectomy with patch angioplasty in terms of morphology and hemodynamics. (January 2022) - Raptis, Anastasios; Tasso, Paola; Batzalexis, Konstantinos; Gallo, Diego; Xenos, Michalis; Morbiducci, Umberto; Giannoukas, Athanasios
Abstract: Background: Carotid endarterectomy (CEA) remains the first-line treatment option of symptomatic and asymptomatic carotid stenosis, while stenting (CAS) is reserved for selected patients at high surgical risk. Here, we compare the vascular remodeling process in CEA- and CAS-treated patients with respect to morphological and hemodynamic features, because of their possible engagement in carotid atherosclerosis. Methods: Twelve (12) patients were included, half with patched CEA and half with CAS. Pre- and post-operative 3D image-based models of the carotid bifurcation were anatomically characterized in terms of flare, tortuosity, and curvature. Individual computational fluid dynamics simulations allowed to quantify the postoperative hemodynamic milieu in terms of (1) wall shear stress and (2) helical flow. Results: Carotid flare increased in all cases, but a more marked increase emerged after CEA compared to CAS. Tortuosity and curvature increased after CEA but decreased after CAS. CEA patients presented with significantly higher postoperative tortuosity than CAS patients. CEA was associated with a worse (non-statistically significant) score in all flow disturbance indicators vs. CAS. Conclusion: The increased flare and tortuosity of the carotid bifurcation after CEA vs. CAS is a marked difference in the vascular remodeling process between the two modalities. CAS seems to induce a less pro-restenosis hemodynamic environment compared to CEA. The emerged differences stimulate further analysis on a larger cohort with long-term outcomes, to shed light on the clinical impact of the observations.